Prevention of mother-to-child-transmission of HIV in Khayelitsha: a contemporary review of services 20 years later - Phelanyane, Florence Malehlabathe (Department of Public Health and Family Medicine, 2022)
Background: It's been 20 years since the Western Cape (WC) province of South Africa launched its first Prevention of Mother-To-Child-Transmission of HIV(PMTCT) pilot programme in Khayelitsha. The programme evolved alongside the World Health Organization (WHO) guidelines; in 2013 the recommended guidelines in the province was WHO Option B+( life-long antiretroviral therapy (ART) irrespective of CD4 count, and exclusive breastfeeding for the first 6 months of life). Alongside the explanation of the PMTCT programme, the province gradually implemented patient administrative systems in all fixed public health facilities; these systems all shared a unique patient identifier called the folder number. The digitization of folder number lead to the establishment of the Provincial Health Data Centre (PHDC), an African health information exchange (HIE) developed and hosted in the WC Department of Health. The HIE also integrated data from disease management information systems (Three Interlinked Electronic Registers (TIER) and the Electronic Tuberculosis Register (ETR)), allowing the ability to track the cohort of pregnant women living with HIV who attend public health services across the Western Cape. Here we report the latest analysis of vertical HIV transmission in the era of WHO Option B+ with the advantage of a maturing consolidated African HIE. The primary aim of the study was to describe coverage of the PMTCT care cascade, including the implementation of maternal viral load monitoring and early infant diagnosis, among HIV positive women who presented antenatal care, or delivered in the absence of antenatal care, at a public health facility in Khayelitsha subdistrict in 2017; and to quantify MTCT risk factors and outcomes among this cohort up to 12 months post-partum. Methods: Patient-level consolidated PHDC data were used to draw an observational cohort consisting of all live-born and linked mother-infant pairs in which the mother was HIV positive, at any point prior to her first antenatal visit up to 12 months post-partum and attended antenatal care, or in the absence of antenatal care delivered in Khayelitsha in 2017. The PHDC provided a single summative record per pregnancy for each woman (linked to her infant after birth) which enabled the assessment of PMTCT uptake from her first antenatal visit through delivery to infant early infant diagnosis (EID) of HIV-PCR testing and PHDC ascertainment of HIV up to the end of the index period (i.e. 12 months post-partum). iii Using this cohort of HIV-exposed infants, a protocol was designed (Section A: Protocol) to assess the outcomes of the implementation of WHO Option B+(lifelong ART for all HIV positive pregnant women; and periodic re-testing of HIV negative women) under the latest EID guidelines of routine birth HIV-PCR (within 1 week of birth), and repeat testing at 10 weeks (between 2 and 14 weeks of birth) or a first HIV-test at 10 weeks if the infant had not been tested at birth. Continuous variables were converted to categorical variables according to pre-set thresholds, all categorical variables were described using proportions, and frequency tables were used for comparison. Timing of ART initiation was categorized as a binary variable which was assigned 1 if the mother started ART before the first antenatal visits, and 0 of she started ART at the first antenatal visit or anytime during the pregnancy. Viral load was categorised according to coverage and suppression status; virologic suppression was defined as having a viral load of 1000 copies/ml or less after 3 months on ART. Analysis was performed in using R studio; descriptive statistics were used to assess coverage along the PMTCT care cascade, and logistic regression was run to quantify a priori defined risk factors associated with MTCT. Results: The study cohort of 2 576 mother-infant pairs (2548 women living with HIV (WLHIV)) presented in the manuscript was a young cohort with a median age of 30 years (interquartile range of 26 – 34), in which most women delivered vaginally (70.5%), and 78.3% attended at least one antenatal visit before delivery. Most WLHIV (88.3%) presented to their first pregnancy related visit (antenatal care or delivery) already knowing their status, of whom 77.9% were already on ART. 94.5% of women diagnosed prior to birth were initiated on ART prior; 85.0% of these women received a viral load test antenatally, of whom 88.0% were virologically suppressed. Early infant diagnosis coverage was sub-optimal with birth HIV-PCR (within 7 days of birth) coverage of 79.21% among HIV exposed infants (HEI); an even lower proportion (57.9%) of HEI who tested negative at birth had a repeat test around 10-weeks. HIV-PCR ascertained MTCT was 0.8% at 10 weeks, consolidated data from the PHDC suggested an MTCT of 1.8% by the end of the index period (the PHDC HIV episode identified an additional 16 HIVexposed (HEI) infants with HIV who were not detected by laboratory tests). PWLHIV who started ART prior to the first antenatal visit had 50% reduced risk of MTCT compared to those who started ART during the pregnancy. Women who were not suppressed antenatally had a 5- fold (aOR = 5.3, 95% CI: 2.5 – 12.3) increased MTCT risk compared to those were suppressed antenatally. Women who did not attend ANC were at highest risk of transmission (aOR=1.6,95%CI: 0.7 – 3.6). iv Conclusion: Although women most women present to care already knowing their HIV status, ART initiation and uptake of viral load testing is very low at presentation but improved significantly during pregnancy, evidence of maturing PMCT services. National and Provincial MTCT is likely to be underestimated as it relies solely on PCR results; the uptake of the birth PCR among HIV-exposed infants is still not 100% (where it should be) and the uptake of a repeat tests among infants that tested negative is even lower. PHDC data, which consolidates HIV data from multiple sources, revealed a higher MTCT than HIV-PCR testing alone.